If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4y + -7x = 0 Reorder the terms: 2x + -7x + 4y = 0 Combine like terms: 2x + -7x = -5x -5x + 4y = 0 Solving -5x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -5x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 -5x + 0 = 0 + -4y -5x = 0 + -4y Remove the zero: -5x = -4y Divide each side by '-5'. x = 0.8y Simplifying x = 0.8y
| 7-(2x+3y-9)= | | 0=5(8+x)+9 | | -(5x-12)+4(3x+7)= | | 6=e/3 | | .144n=27 | | -9x+8=3x-4 | | 27.5n=17.16 | | 5x+19=43-7x | | 0=x+(4+3x)7 | | 8x-14+6x-2=180 | | 8x-14+6x-2= | | -10+x+x+4-5=7x-5 | | 3x+8y=23forx | | 4/1=11/c | | -9(5a-8)+(9q-6)= | | 4m-29=-28+3m | | 0=4+(8x+9)2 | | X^2+27x+169= | | 7s-7=-47+2s | | x^4+x^2-90= | | 40(x-20)=20(6) | | 7(1-8x)=7+2x | | 3x^5+3x^4-15x^3+6x^2=0 | | x-1/15=2/15 | | 0=x+5(5x+1) | | (y-2)(y+1)= | | x^6-90= | | x−1/15=2/15 | | 3=x3/3 | | 3=x/3/3 | | X^2+25x+141= | | x-1/10=615 |